Oxidative Desulfurization of Dibenzothiophene in a Micro-Structured Reactor - Hu, S.Z.; Li, F.Y.; Fan, Z.P. (Asian Journal of Chemistry, 2011)
It is known that the desulfurization process has great potential to be a complementary process to traditional hydrodesulfurizaion for producing deeply desulfurized diesel fuel. However, the traditional batch reactor system needs a long reaction time and high O/S molar ratio to achieve high conversion. In the present work, a micro-structured reactor system was used to investigate the oxidative desulfurization performance of dibenzothiophene. The results indicated that more than 90 % dibenzothiophene was oxidated within 3 min. The excellent mass transport capability of micro-structured reactor lead the dibenzothiophene oxidation carried out under stoichiometric ratio.